Performance of reinforced concrete buildings and wooden structures during the 2015 Mw 6.0 Sabah earthquake in Malaysia. (August 2019) - Alih, Sophia C.; Vafaei, Mohammadreza
Abstract: This paper discusses the outcome of an investigation which was conducted soon after the 2015 Sabah earthquake in Malaysia. Buildings in the affected area were mainly constructed from reinforced concrete (RC) and wooden materials. Although the Mw 6.0 earthquake imposed significant damage to the majority of RC buildings, no significant structural damage was observed for the wooden structures. It was found that damage to the RC buildings was mainly because of non-ductile detailing of the structural components, strong-beam weak-column condition, captive-column and short-column effects, soft and weak stories mechanism, irregularity in plan and elevation, unconfined gable/infill walls, bad workmanship, and the low quality of construction materials. It was observed that many wooden structures had flaws in their design and construction as well. However, because of the high strength-to-weight ratio and the flexible properties of wooden materials which allow them to undergo several cycles of deformation without breaking, they survived the seismic actions. This paper identifies and discusses the main reasons for the damage observed in RC buildings and the construction flaws that were observed for wooden structures. Recommendations from seismic design codes in order to prevent the occurrence of such damage in the future are also highlighted. Highlights: A brief explanation about seismic activities in Sabah, Malaysia is presented. Observed damage to RC buildings and seismic code requirements are discussed. Damage to wooden buildings and observed construction flaws are discussed. Suggestions for having safer structures in the future construction are provided.